Invitro Assessment Of Anti Oxidant And Anti-Inflammatory Properties Of Centella Asiatica Aqueous Leaf Extract - Charunivedha, S.; Jeba Malar, T. Renisheya Joy (Journal of Neonatal Surgery, 2025)
Centella asiatica (L) is one of the important medicinal plants in the International market of medicinal Plant Trade. Medicinal plants have been used all over the world as unique sources of medicines and may constitute the most common human use of biodiversity. A numbers of phytochemicals have been isolated from the various extracts of the plant. These include terpenoids, phenolic compounds, poly acetylenes, alkaloids, carbohydrates, vitamins, mineral and amino acid. The plant is attributed to possess a number of therapeutic uses such as antimicrobial, anti-inflammatory, astringent, bronchodilator, CNS-depressant, de-toxicant, diuretic, immune stimulant, anticancer and hepato-protective etc. The antioxidant activity of Centella plays a key role in acting against the reactive oxygen species in our body. Due to health benefits like antioxidant activity, the usage of Centella in food and beverages has been increased over these years. The use of Centella in food and beverages has increased over the years. The knowledge regarding ability of Centella as an alternative natural antioxidant especially of plant origin and its protection against age-related changes in brain antioxidant defense system, memory enhancing property has increased in recent years. In the present study, the antioxidant and Antiinflammatory property of fresh Aqueous Extract of C. asiatica was studied and the present research reported aqueous extract of Centella asiatica recognized minimum antioxidant and antitinflammatory property compared to the standards.